2017
DOI: 10.3390/toxins9010021
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Zearalenone Exposure Causes Reproductive and Developmental Toxicity in Pregnant Rats and Female Offspring

Abstract: Zearalenone (ZEN) is an oestrogenic mycotoxin commonly found in food and feed products and can affect reproduction and development in both humans and animals. This study aimed to determine the toxic effects of ZEN on maternal SD rats and the F1 female offspring. Sixty-four pregnant rats were divided into 4 groups and exposed to feed contaminated with ZEN (0, 5, 10, and 20 mg/kg feed) on gestational days (GDs) 0–21. Compared with the controls, the groups exposed to 10 and 20 mg/kg ZEN showed significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 59 publications
0
27
0
1
Order By: Relevance
“…Both ZEN and DON are mainly produced by Fusarium . ZEN is an estrogenic toxin that competes with 17 β-estradiol for estrogen receptor binding, which consequently leads to fertility and reproductive problems [ 8 , 9 ]. In contrast, DON can induce anorexia, vomiting, and impairs immune function in various livestock species that involves inhibiting DNA, RNA, and protein synthesis [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both ZEN and DON are mainly produced by Fusarium . ZEN is an estrogenic toxin that competes with 17 β-estradiol for estrogen receptor binding, which consequently leads to fertility and reproductive problems [ 8 , 9 ]. In contrast, DON can induce anorexia, vomiting, and impairs immune function in various livestock species that involves inhibiting DNA, RNA, and protein synthesis [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This situation is also implicated in studying the effect of ZEA on placental development. Several studies have alluded to the placenta as a target of ZEA: for example, ZEA can be bioactivated in placental cells [20]; ZEA and its metabolites can pass through placentas [21,22]; ZEA (2.76 ppm diet from D35 to D70 of pregnancy) can be accumulated in pig placentas and reduce placental and fetal weights [23], which may indicate impaired placental function that was not further investigated in the study; ZEA (20 ppm diet, from D0.5 to D20.5 of pregnancy) causes reduced birth weight of rats and reduced Esr1 (ERα) mRNA levels in the placentas but its effects on placental weight and placental morphology were not reported in the study [24]; rats exposed to 8 mg/kg body weight ZEA via gavage on D6-D19 had increased resorption of implantation sites and decreased fetal viability examined on D20, but the placentas were not examined in the study [25]. Since the placenta is the sole source of nutrients for supporting fetal development, the fetal toxicity from ZEA treatment could be a secondary effect of placental toxicity.…”
Section: Introductionmentioning
confidence: 82%
“…In mammalians, CCNA1 appears to be stage-specific and highly expressed in germ cells [31,43]. ABCC1 is widely expressed in various tissues and plays an important role in uteroplacental transport signaling [44,45]. In addition, it was reported that the hypothalamic–pituitary–gonadal axis (HPG) is the most important system for controlling mammalian reproduction [46].…”
Section: Discussionmentioning
confidence: 99%